'Scandalus to all us': presenting an anti-alehouse petition from late Elizabethan Rickmansworth (Hertfordshire). Issue 1 (April 2020) - Falvey, Heather
Abstract: In the early summer of 1588, twenty-seven inhabitants of the large parish of Rickmansworth (Hertfordshire) presented a petition to two local Justices of the Peace complaining about disorder in Mill End, on the outskirts of the main town, caused by those frequenting Richard Heyward's alehouse. Most recent work on alehouse sociability has considered attitudes towards drinking and its regulation after the early Jacobean legislation; in contrast, this article considers attitudes towards drunkenness in late sixteenth-century England, including the views expressed in the official 'homily against drunkenness' and in the Sabbatarian pamphlet published in 1572 by Humfrey Roberts. Similarly, most work on early modern protest considers complaints against the activities of the protestors' social superiors; in this instance petitioners complained about the conduct of their inferiors. Although, due to archival attrition, it is impossible to determine what action the authorities took against Heyward and his clientele, thanks to the chance survival of a personal letter it is possible to reconstruct the reactions of the JPs to whom the petition was addressed, thus shedding light on how JPs might act outside the Quarter Sessions.